Mono-WNV and combined WNV/TBEV inactivated vaccine efficacy against a wide range of WNV and TBEV strains - Tuchynskaya, Ksenia; Vorovitch, Mikhail; Kruglov, Yuriy; Mostipanova, Guzal; Kholodilov, Ivan; Ivanova, Alla; Kuchina, Victoria; Rogova, Anastasia; Karganova, Galina (Frontiers in Immunology, 2025)
West Nile virus (WNV) is widespread throughout the world. Occasionally, it causes outbreaks of the West Nile fever (WNF) disease, which can lead to severe CNS damage or death. At the same time, the virus’ expanding range is increasingly leading to the formation of mixed foci with other orthoflaviviruses, such as tick-borne encephalitis virus (TBEV). Based on long-term experience using inactivated vaccines to target tick-borne encephalitis (TBE), it seems sensible to create a complex inactivated vaccine targeting two antigens to protect the population against several orthoflaviviruses at once. The immunogenicity and efficacy of the mono-WNV and combined WNV/TBEV inactivated vaccines—based on WNV strain SHUA-3 and TBEV strain Sofjin against a wide range of WNV and TBEV strains—were compared in an in vitro neutralization assay, as well as in BALB/c mice in vivo. The mono vaccines showed a lack of cross-immunogenicity and protection, whereas the combined vaccine was immunogenic against five WNV strains of lineages 1 and 2 and five TBEV strains belonging to different virus subtypes. In the mouse model, the mono-WNV vaccine was effective against the three most pathogenic strains of WNV used in this work, while the combined WNV/TBEV vaccine was effective against both WNV and TBEV. Our work shows promise for the further development of a combined vaccine against WNF and TBE.